(3QjGV GdfahS aj WHbGJ abgGA eOjfI GdbjQhGfs - (3CHh HcQ YHO Gddg Hf eMeO Hf YHO Gddg GdeGdcj, GdeGdcj,J (B453 (3g` s
(3ChdgG (B:s
(3hajgG Jhai CHh YbGd Hf YdhGf QVi Gddg Yfg , Jhai hgh SGLO Nda GdebGe s
(3BNQgG (B:s
(3faYfG Gddg SHMGfg YR hLd Hge BNQ cJGH QjGV GdfahS ai WHbGJ YdeGA eOjfI GdbjQhGf s
(3GfXQ Qbe (B690s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B121s
Keywords: (3GdJGQjNs